Hunger, Food Sovereignty and COVID-19 Pandemic: Food Risks During Lockdown - Mónica Juliana Chavarro; Janeth Mosquera-Becerra (Frontiers Media S.A., 2023)
Objective: This article focuses on describing the food scenario of families in Cali (Colombia), where almost half of the city's population could not guarantee their access to adequate feeding during COVID-19 crisis.Methods: Involved 1. Analyze laws to understand their relationship with access to food in Cali during lockdown; and 2. Identify changes in the eating practices of families from different socioeconomic levels and the strategies used by the city's public institutions during lockdown.Results: Feeding was not considered from the beginning of the lockdown, which generated a food crisis. Institutional responses were insufficient in quality and coverage, since feeding aid focused on calories and logistic aspects. The solutions implemented by households were guided by collective action and social organization around the community pots.Conclusion: The contrast between food security strategies (focused on availability and access) and food sovereignty (with an emphasis on the collective) shows the need for structural transformations in food policies and in the collective imagination that allow for designing new food models focused on community wellbeing and not on economic growth to future emergencies.